Opportunities and challenges of applying advanced X‐ray spectroscopy to actinide and lanthanide N‐donor ligand systems. (21st December 2021) - Pruessmann, Tim; Nagel, Peter; Simonelli, Laura; Batchelor, David; Gordon, Robert; Schimmelpfennig, Bernd; Trumm, Michael; Vitova, Tonya
Abstract : Exploring the opportunities and challenges when studying actinide and lanthanide N‐donor ligand systems relevant for separation technologies from the metal and ligand point of view using X‐ray spectroscopy techniques and computations. Abstract : N‐donor ligands such as n ‐Pr‐BTP [2, 6‐bis(5, 6‐dipropyl‐1, 2, 4‐triazin‐3‐yl)pyridine] preferentially bind trivalent actinides (An 3+ ) over trivalent lanthanides (Ln 3+ ) in liquid–liquid separation. However, the chemical and physical processes responsible for this selectivity are not yet well understood. Here, an explorative comparative X‐ray spectroscopy and computational ( L 3 ‐edge) study for the An/Ln L 3 ‐edge and the N K ‐edge of [An/Ln( n ‐Pr‐BTP)3 ](NO3 )3, [Ln( n ‐Pr‐BTP)3 ](CF3 SO3 )3 and [Ln( n ‐Pr‐BTP)3 ](ClO4 )3 complexes is presented. High‐resolution X‐ray absorption near‐edge structure (HR‐XANES) L 3 ‐edge data reveal additional features in the pre‐ and post‐edge range of the spectra that are investigated using the quantum chemical codes FEFF and FDMNES . X‐ray Raman spectroscopy studies demonstrate the applicability of this novel technique for investigations of liquid samples of partitioning systems at the N K ‐edge.